1995
DOI: 10.1212/wnl.45.2.317
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐sectional area of the posterior hippocampus in autistic patients with cerebellar and corpus callosum abnormalitiGs

Abstract: Using MRI methods previously shown to optimize visualization of cytoarchitectonic details in the body of the hippocampal formation caudal to the pes hippocampi, we imaged and quantified the hippocampus proper including the subiculum and the dentate gyrus in 33 autistic patients between the ages of 6 and 42 years and in 23 age-matched normal healthy volunteers. Measures of these structures in autistic patients and normal healthy volunteers differed nonsignificantly, by less than 1.4%, regardless of whether or n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0
3

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(52 citation statements)
references
References 1 publication
2
47
0
3
Order By: Relevance
“…It is believed that genu fibers can be mapped to prefrontal cortical areas (Witelson, 1989). Our results are in good agreement with the literature (Courchesne, Press, & YeungCourchesne, 1993;Hardan, Minshew, & Keshavan, 2000;Manes et al, 1999;Piven, Bailey, Ranson, & Arndt, 1997;Saitoh, Courchesne, Egaas, Lincoln, & Schreibman, 1995), and they were obtained in the context of lowered functional connectivity in the autism group.…”
Section: Corpus Callosum Sizesupporting
confidence: 92%
“…It is believed that genu fibers can be mapped to prefrontal cortical areas (Witelson, 1989). Our results are in good agreement with the literature (Courchesne, Press, & YeungCourchesne, 1993;Hardan, Minshew, & Keshavan, 2000;Manes et al, 1999;Piven, Bailey, Ranson, & Arndt, 1997;Saitoh, Courchesne, Egaas, Lincoln, & Schreibman, 1995), and they were obtained in the context of lowered functional connectivity in the autism group.…”
Section: Corpus Callosum Sizesupporting
confidence: 92%
“…Studies investigating CC anomalies in autism have employed structural MRI to find reductions in area on the midsagittal plane as well as in volumetric measures. Results include overall decreases in midsagittal area (Boger-Megiddo et al, 2006;Manes et al, 1999;Vidal et al, 2006), and subregional decreases in in the anterior (Hardan, Minshew, & Keshavan, 2000;Just, Cherkassky, Keller, Kana, & Minshew, 2006;Vidal et al, 2006), middle Piven, Bailey, Ranson, & Arndt, 1997), and posterior (Just et al, 2006;Saitoh, Courchesne, Egaas, Lincoln, & Schreibman, 1995;Waiter et al, 2005) portions of the CC. The majority of nonstatistically significant results from these studies also showed a trend towards a decrease in area in all subregions.…”
Section: Corpus Callosummentioning
confidence: 99%
“…The combined findings of ten structural MRI studies yield no consistent pattern, with a near equal distribution of increased, decreased, and non-significant differences in hippocampal volumes. The first five stu- Schumann et al (2004) employed HFA, LFA, and AS subgroups; Saitoh et al (1995) and Saitoh et al (2001) employed partial LFA subgroup.…”
Section: Hippocampusmentioning
confidence: 99%
See 1 more Smart Citation
“…Em oposição ao que se observa no TDAH, pacientes autistas apresentam aumento do volume total do cérebro e também específico de regiões como o cerebelo, o caudado e o globo pálido (Piven et al, 1996). Ambos, entretanto, apresentam diminuição do corpo caloso (Saitoh et al, 1995). Em estudos de neuroimagem funcional, o achado que sobressai é a reduzida ativação das regiões frontotemporais em autistas (Baron-Cohen et al, 1999), o que também ocorre em pacientes com TDAH.…”
Section: Conclusãounclassified